2013
DOI: 10.1038/cr.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

Genome editing with RNA-guided Cas9 nuclease in Zebrafish embryos

Abstract: Recent advances with the type II clustered regularly interspaced short palindromic repeats (CRISPR) system promise an improved approach to genome editing. However, the applicability and efficiency of this system in model organisms, such as zebrafish, are little studied. Here, we report that RNA-guided Cas9 nuclease efficiently facilitates genome editing in both mammalian cells and zebrafish embryos in a simple and robust manner. Over 35% of site-specific somatic mutations were found when specific Cas/gRNA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
536
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 735 publications
(555 citation statements)
references
References 23 publications
3
536
0
2
Order By: Relevance
“…A recent study showed that generation of robust biallelic mutations by CRISPR/ Cas9 system in the injected zebrafish embryos appears to allow for phenotypic analysis directly in the F0 animals [27]. To further confirm the function of NudC during zebrafish development, we designed a guide RNA (gRNA) to target zebrafish NudC.…”
Section: Nudc Knockdown Results In Ciliary Phenotypes In Zebrafishmentioning
confidence: 99%
“…A recent study showed that generation of robust biallelic mutations by CRISPR/ Cas9 system in the injected zebrafish embryos appears to allow for phenotypic analysis directly in the F0 animals [27]. To further confirm the function of NudC during zebrafish development, we designed a guide RNA (gRNA) to target zebrafish NudC.…”
Section: Nudc Knockdown Results In Ciliary Phenotypes In Zebrafishmentioning
confidence: 99%
“…Technologies of ZFN and TALEN have made genetargeting in the rat genome more convenient and practical [7][8][9]. The CRISPR/Cas system is the most recently developed technology for targeted genome modification in mammalian cells, bacteria, zebrafish and mice [10][11][12]. This system requires a locus-specific CRISPR RNA (crRNA), a transactivating crRNA (tracrRNA) and a nuclease Cas9.…”
Section: Dear Editormentioning
confidence: 99%
“…Over 35% of site-specific mutations were found when specific Cas/gRNA was used to target genes in living zebrafish embryos. The study also successfully achieved site-specific insertion of mloxP sequence induced by Cas9/gRNA system in zebrafish embryos, and showed that the Cas9/gRNA system has the potential to be a simple and efficient reverse genetic tool for zebrafish and other model organisms [20].…”
Section: Potential For Therapies Based On the Crispr-cas Systemmentioning
confidence: 92%